Heterogeneity of Red Blood Cells: Causes and Consequences - Bogdanova, Anna; Kaestner, Lars; Simionato, Greta; Wickrema, Amittha; Makhro, Asya (Frontiers in Physiology, 2020)
Mean values of haematological parameters are currently used in the clinical laboratory settings to characterise red blood cell properties. Those include red blood cell indices, osmotic fragility test, eosin 5-maleimide (EMA) test, and deformability assessment using ektacytometry to name a few. Diagnosis of hereditary red blood cell disorders is complemented by identification of mutations in distinct genes that are recognised “molecular causes of disease”. The power of these measurements is clinically well-established. However, the evidence is growing that the available information is not enough to understand the determinants of severity of diseases and heterogeneity in manifestation of pathologies such as hereditary hemolytic anaemias. This review focuses on an alternative approach to assess red blood cell properties based on heterogeneity of red blood cells and characterisation of fractions of cells with similar properties such as density, hydration, membrane loss, redox state, Ca2+ levels, and morphology. Methodological approaches to detect variance of red blood cell properties will be presented. Causes of red blood cell heterogeneity include cell age, environmental stress as well as shear and metabolic stress, and multiple other factors. Heterogeneity of red blood cell properties is also promoted by pathological conditions that are not limited to the red blood cells disorders, but inflammatory state, metabolic diseases and cancer. Therapeutic interventions such as splenectomy and transfusion as well as drug administration also impact the variance in red blood cell properties. Based on the overview of the studies in this area, the possible applications of heterogeneity in red blood cell properties as prognostic and diagnostic marker commenting on the power and selectivity of such markers are discussed.